Motivation Trumps Placement as the Key to Boosting Employee Performance in Indonesia: Motivasi Mengalahkan Penempatan sebagai Kunci untuk Meningkatkan Kinerja Karyawan di Indonesia - Ananda Erviana Putri; Dewi Andriani (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the impact of competency, job placement, and work motivation on employee performance at Perumda Delta Tirta Sidoarjo. Using a quantitative approach with a sample of 222 employees selected through simple random sampling, the research employed multiple regression analysis and hypothesis testing via SPSS 26. Results indicate that both competency and work motivation positively influence employee performance, while job placement does not have a significant impact. Overall, competency, job placement, and work motivation collectively affect performance, with work motivation being the most influential factor. The findings suggest that enhancing competency and motivation can improve performance, and job placement strategies should better match individual capabilities. Highlights: Competency boosts performance: Competency significantly enhances employee performance. Job placement's impact: Job placement does not significantly affect performance. Motivation matters most: Work motivation is the dominant performance factor. Keywords: Competency, Job Placement, Work Motivation, Employee Performance, Quantitative Study